2006
DOI: 10.1590/s0034-89102006000200013
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade por câncer em trabalhadores da indústria da borracha de São Paulo

Abstract: OBJECTIVE:To investigate cancer deaths among rubber industry workers according to company size. METHODS:This historical cohort study included 9,188 male workers, engaged as members of a workers ' union in São Paulo, Southeastern Brazil, between 1975 and 1985, alive in January 1990 and followed until the end of 2000. Overall and specific cancer deaths were compared within the cohort, with subjects stratified according to company size and economic activity, sector of work, and worker qualification. Risk set ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…These cases accounted for 6.0% of all cancers identified in the study: three times higher than expected. 61 Asbestos, vulcanization fumes and, particularly, nitrosamines have been considered as the possible causative agents of cancer in the rubber industry, in addition to naphthylamine. 60 A case-control study from the United States found risk factors of more than 3.0 for railroad industry workers, sheet metal workers, grinding wheel operators and automobile mechanics.…”
Section: Occupationmentioning
confidence: 99%
“…These cases accounted for 6.0% of all cancers identified in the study: three times higher than expected. 61 Asbestos, vulcanization fumes and, particularly, nitrosamines have been considered as the possible causative agents of cancer in the rubber industry, in addition to naphthylamine. 60 A case-control study from the United States found risk factors of more than 3.0 for railroad industry workers, sheet metal workers, grinding wheel operators and automobile mechanics.…”
Section: Occupationmentioning
confidence: 99%
“…La variable temporal de la exposición ocupacional a los factores cancerígenos necesita ser considerada para las investigaciones, ya que los trabajadores con mayor tiempo de actuación en el trabajo y, consecuentemente, mayor probabilidad de exposición a sustancias cancerígenas tienen mayor probabilidad de desarrollar cáncer. Los trabajadores que iniciaron la actividad en la industria, por ejemplo, hace más de veinte años presentaron asociación positiva con diferentes muertes por cáncer 15 . Aunque son significativas las características relacionadas con el diagnóstico, en lo que se refiere a la exposición a las radiaciones no ionizantes, las evidencias aún no son conclusivas al respecto.…”
Section: Discussionunclassified
“…Farmers and rubber tappers skin and airways are easily exposed to these agents as solar radiation, pesticides, solvents, fumes and gases containing hydrocarbons and benzene during the work time. There is considerable evidence of accumulation on the carcinogenic action of these chemicals used in agriculture, especially pesticides 14,16 . The International Agency for Research on Cancer (IARC) 12 recognizes sufficient evidence on the carcinogenicity of 18 pesticides and other evidence to 16.…”
Section: ▄ Discussionmentioning
confidence: 99%
“…Organochlorines, chemical products that we can find in pesticides, belong to Group 2B carcinogens by IARC, DDT, dichlorodiphenyltrichloroethane, and are associated with the development of liver cancer, lung and lymphoma in laboratory animals 6 . In the case of solar radiation and rubber industry agents, classified in Group I, there are sufficient evidence of carcinogenicity in human beings 12,16 . According to the World Health Organization, developing countries consume 20% of all pesticides produced in the world 15 …”
Section: ▄ Discussionmentioning
confidence: 99%